Zoledronic acid as potential efficacy application combined with icotinib for non-small cell lung cancer with bone metastases - Wang, Wenxian; Song, Zhengbo; Zhang, Yiping (Translational Cancer Research; Vol 6, No 1 (February 27, 2017): Translational Cancer Research (Focused Issue: Advances on Clinical Immunotherapy), 2017)
Background: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) are now widely used to treat EGFR mutated non-small cell lung cancer (NSCLC), with icotinib being one such EGFRTKI. The incidence of bone metastases ranges from 30% to 40 % in patients with NSCLC. Zoledronic acid is a third-generation bisphosphonate. Some reports have described the possibility of direct and indirect antitumor effects of zoledronic acid. Methods: We retrospectively evaluated survival data of 171 patients who received icotinib with progression-free survival (PFS) more than 6 months and received zoledronic acid at least once from July 2011 to May 2015 in Zhejiang cancer hospital. And we analyzed PFS and overall survival (OS) by the Kaplan-Meier method. Multivariate regression was assessed by the Cox proportional hazards model. Results: We enrolled 171 NSCLC patients with bone metastases were treated with zoledronic acid and icotinib. A total of 133 (77.8%) patients were with EGFR-mutated (72 with deletions in exon 19, 59 with L858R mutation in exon 21 and 2 with G719X mutation in exon 18). Median Progression free survival (mPFS) of all patients during icotinib treatment was 11.0 months. And median overall survival (mOS) was 24.6 months. PFS in group of ≥1 year, between 1 year and 6 months group, and group of